Optimalisasi Pemanfaatan Sumber Daya Lokal Berbasis Pengolahan Pangan di Desa Mantingan, Kecamatan Jaken, Kabupaten Pati - Muhammad Aushol Amri; Aisyah Nurrismiyandini; Mellania Chandra Dewi; Ika Feby Astuti; Sumi Jayanti; I Wayan Astika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Community empowerment needs to be realized to increase the independence of village communities. Community empowerment activities in the village of Mantingan, especially KWT Al-Ikhlas, can improve knowledge and skills related to the processing of chili and shallot agricultural products, as well as take advantage of the telang flower which is rich in benefits. The method of implementation is carried out in several activities, namely discussions with partners, trials of making chili and siwang powder, training in making chili and siwang powder, planting telang flowers, and making agricultural product brands. The community prefers to sell chilies and shallots directly to collectors even when the price of chilies and shallots drops. The community considers the telang plant to be a wild plant because they do not know the benefits of the telang flower. Making chili powder is done to overcome the price of chili which tends to fluctuate and extend the self-life of the chilies being harvested. The innovation in processing chili powder